International Market Entry and Development: Are European SMEs ready to China? Author: Feng Lu - FENG, LU (2014)
Over the last decade internationalization business has increased dramatically, especially among some fast growing international markets. At the microenvironment and industry level, internationalization brings a rise to market turbulence, increase competition of firms, loss of a protected market due to international trade, furthermore give companies much more opportunities and challenges (Adam, 2006). Within the environment of internationalization, a large number of small and medium size enterprises (SMEs) start approaching global market, however, what internationalization process is more suitable for them and which entry form is matching their occasion. A several of problems are facing to SMEs internationalization progress.